Self-emulsifying Drug Delivery System: A Review: Self-emulsifying Drug Delivery System: A Review - Rajpoot, Dr. Ashok Kumar (International Journal of Pharmaceutical & Biological Archive, 2019)
Drug development in the past used to be initiated after the identification of most active molecule. However, this approach leads to a number of drawbacks with the problems being that many molecules which are put into development had poor physicochemical such as solubility and stability and biopharmaceutical such as permeability and enzymatic stability properties, as a consequence of which about 40% of new chemical entities fail to reach the market place. At present, a number of technologies are available to deal with the poor solubility, dissolution rate, and bioavailability of insoluble drugs. However, much attention has been focused on lipid-based formulations, with particular emphasis on self-emulsifying drug delivery systems (SEDDSs). SEDDSs are defined as isotropic mixtures of natural or synthetic oils, solid or liquid surfactants, or one or more hydrophilic solvents and cosolvents/surfactants. On mild agitation followed by dilution in aqueous media, these systems can form fine oil-in-water emulsions or microemulsions (self-micro-EDDS [SMEDDS]). Self-emulsifying formulations spread readily in the gastrointestinal tract, the digestive motility of the stomach and intestine provides the agitation necessary for self-emulsification. SEDDSs produce emulsification with a droplet size between 100 and 300 nm, while SMEDDSs form transparent microemulsions with a droplet size of <50 nm. SEDDSs are physically stable formulations that are easy to manufacture. Thus, for lipophilic drug compounds that exhibit dissolution rate-limited absorption, these systems may offer an improvement in the rate and the extent of absorption.